Resolving Faculty Incivility and Workplace Bullying in Higher Education - Jared Rawlings (Academic Chairpersons Conference Proceedings, 2023)
Workplace bullying behavior exists in higher education and the purpose of this session is to present current research about bullying behaviors, explain the impact of bullying between and among populations (faculty and staff), explicate legal and ethical issues, and model practices for academic chairpersons to address bullying behaviors.
Keywords: Workplace Bullying; Higher Education; Faculty; Support Staff; Incivility